2014
DOI: 10.1095/biolreprod.113.116418
|View full text |Cite
|
Sign up to set email alerts
|

Oviduct Binding and Elevated Environmental pH Induce Protein Tyrosine Phosphorylation in Stallion Spermatozoa1

Abstract: Sperm-oviduct binding is an essential step in the capacitation process preparing the sperm for fertilization in several mammalian species. In many species, capacitation can be induced in vitro by exposing spermatozoa to bicarbonate, Ca 2+ , and albumin; however, these conditions are insufficient in the horse. We hypothesized that binding to the oviduct epithelium is an essential requirement for the induction of capacitation in stallion spermatozoa. Sperm-oviduct binding was established by coincubating equine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 78 publications
(114 reference statements)
1
28
1
3
Order By: Relevance
“…While changes in the membrane fluidity and membrane destabilization of the sperm plasma membrane induced by bicarbonate have been shown to be immediate [5], it may be possible that dog sperm are more susceptible to prolonged periods of incubation, inducing membrane destabilization as detectable by M540-YP even in the absence of bicarbonate. Recent studies on stallion sperm have shown that an increase in the pH of the incubation medium induces capacitation (46). Unfortunately the pH of the media used in the current study was not monitored in order to detect a change therein.…”
Section: Discussionmentioning
confidence: 95%
“…While changes in the membrane fluidity and membrane destabilization of the sperm plasma membrane induced by bicarbonate have been shown to be immediate [5], it may be possible that dog sperm are more susceptible to prolonged periods of incubation, inducing membrane destabilization as detectable by M540-YP even in the absence of bicarbonate. Recent studies on stallion sperm have shown that an increase in the pH of the incubation medium induces capacitation (46). Unfortunately the pH of the media used in the current study was not monitored in order to detect a change therein.…”
Section: Discussionmentioning
confidence: 95%
“…Unfortunately, heparin-like glycosaminoglycans have no capacitation-inducing effects on stallion spermatozoa [40]. Using the oviduct explant model, however, we found that in vitro binding of stallion spermatozoa to oviduct epithelium was able to induce capacitation [38]. Oviduct-bound spermatozoa showed a time-dependent protein tyrosine phosphorylation response that was not observed in unbound spermatozoa or when spermatozoa were incubated in oviduct explant-conditioned medium.…”
Section: Capacitation Of Stallion Spermatozoa In An Oviduct Explant Mmentioning
confidence: 79%
“…oviduct binding, while a time-dependent gradual increase in intracellular pH was observed in oviduct-bound spermatozoa; unbound spermatozoa did not show intracellular pH changes [38].…”
Section: Capacitation Of Stallion Spermatozoa In An Oviduct Explant Mmentioning
confidence: 82%
See 2 more Smart Citations